TARI JANGKRIK NGENTHIR DALAM UPACARA BERSIH DESA DI DESA JRAKAH KECAMATAN SELO KABUPATEN BOYOLALI - Rochmad Haryadi (Pascasarjana Institut Seni Indonesia Surakarta, 2009)
Jangkrik solar parade Ngenthir grows up and amends at environmentally Jrakah’s Silvan society as ceremony of executed silvan clear exactly with breakfast tradi- tion. Clear ceremony tradition life dea is done up to fifty years hand in glove relationship it with social cultural its supporting. How forms parade dance in ritual’s ceremony clean slate village at Silvan Jrakah, Cello district, Boyolali’s regency Are solar fashioned meaning Jangkrik Ngenthir in that ritual’s ceremony? That phenomenon, having energy draw for observed in a research. Therefore problem formulation is proposed to work through about problem utilized by kualitatif ’s description method with tech studi’s data collecting library, observa- tion and interview.Silvan clear ceremony one demonstrates to Jangkrik Ngenthir dance that did by religious full magis to look after silvan society viability Jrakah as prop it.Form of Jangkrik Ngenthir comprises one of supported group type four dancer rides on horseback kepang, one Penthul’s dancer, one Tembem’s dancer, one Bel- lyband dancer, four Pengrawit, meanwhile property that is utilized which is horse kepang. Meaning that consists in to paradeJangkrik Ngenthir dance constitute fecundity and safety ceremony for Jrakah’s Village society. Keywords: Jangkrik Ngenthir, ritual’s ceremony